Electronic pathways in photoactivated repair of UV mutated DNA - Bohr, H.; Jalkanen, Karl; Malik, F. (World Scientific Publishing Company, 2005)
An investigation of the physics, underlying the damage caused to DNA by UV radiation and its subsequent repair via a photoreactivation mechanism, is presented in this study. Electronic pathways, starting from the initial damage to the final repair process, are presented. UV radiation is absorbed to create a hole-excited thymine or other pyrimidine that subsequently is responsible for the formation of a dimer. The negative-ion of the cofactor riboflavin, FADH-, formed by the exposure of the photolyase protein to visible light, interacts with the hole-excited electronic orbital of the thymine dimer inducing a photon-less Auger transition, which restores the two thymines to the ground state, thereby detaching the lesion and repairing the DNA. Density functional theoretical calculations supporting the theory are presented. The mechanism involves the least amount of energy dissipation and is charge neutral. It also avoids radiation damage in the repair process. Recent experimental data are compatible with this theory.